PENERAPAN STRATEGI PEMBELAJARAN COOPERATIVE TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD)TERHADAP KEMAMPUAN MENGANALISIS UNSUR PEMBANGUN PUISI PADA SISWA KELAS X SMA NEGERI 8 LUBUKLINGGAU - Cantika, Desi; Satinem; Murti, Sri (LP3MKIL, 2025)
The aim of this research is to determine the significant completeness of the ability to analyze the building blocks of poetry texts for class The research method used was sampling using the saturated sampling technique. Data collection was carried out using test techniques. The collected data was analyzed using the t-test at a significance level of α = 0.05. The results of data analysis can be found tcount = ˃ 3.9476 ttable = 1.71, so it can be concluded that the ability to analyze the building blocks of poetry texts for students at SMA Negeri 8 Lubuklinggau after implementing the student teams achievement division (STAD) type cooperative learning strategy is significantly complete.